Estrategias neurocognitivas para abordar el trastorno de déficit de atención más hiperactividad en los niños de cuarto año de educación general básica de la unidad educativa Roberto Alfredo Arregui” de la ciudad de Guaranda, provincia Bolívar, periodo 2023- 2024. - Estrada Salazar, José Manuel (2024)
Our research focused on how to implement neurocognitive strategies in children as a tool to enhance the learning of fourth-grade students at 'Roberto Alfredo Arregui' Basic General Education. Similarly, guide teachers, who are a pivotal axis in creating a general knowledge for children, were involved in this study. Attention Deficit Hyperactivity Disorder (ADHD) is a neurobiological condition that affects attention, impulsivity, and motor activity, and can significantly impact the academic, social, and emotional functioning of affected students. In recent years, the use of neurocognitive strategies as an alternative or complement to traditional cognitive development for ADHD has been explored. These strategies include attention training, executive function training, among others. This executive summary reviews the available scientific evidence on the effectiveness of these neurocognitive strategies in managing ADHD. It highlights that while some interventions have shown promise in improving ADHD symptoms and children's functionality, there are still limitations in terms of the consistency of results and the generalization of findings. The need for continued research in this field is emphasized, with well-designed studies that address individual differences in treatment response, the durability of effects, and the comparison of the relative efficacy of different neurocognitive strategies. Additionally, the importance of integrating these interventions within a multidisciplinary and personalized approach to the comprehensive treatment of ADHD is underscored. This approach should consider the specific needs of each student and promote their long-term well-being.